First clinical evaluation of a new single-use flexible ureteroscope (LithoVue): a European prospective multicentric feasibility study - Doizi, Steeve; Knoll, Thomas (World journal of urology, 2017)
Introduction: We evaluated a new digital single-use flexible ureteroscope, LithoVue with respect to deflection, image quality and maneuverability. Methods: A prospective cohort study was conducted in eight tertiary reference centers in Europe in December 2015 and January 2016. All consecutive patients included underwent flexible ureteroscopy and were 18 years or older. Deflection and image quality pre- and post-use and maneuverability were rated with a Likert scale. Results: A total of 40 procedures were performed (five per institution). The indication for FURS was treatment of renal stones in 92.5 % of the cases. Before LithoVue usage, the median measured upward and downward deflections were both 270°. Image quality was rated as “very good” in 65 % of cases and “good” in 30 %. Maneuverability was “very good” in 77.5 % and “good” in 17.5 %. At the final evaluation, median upward and downward deflections were both 270°. Image quality was still “very good” in 65 % of cases and “good” in 30 % with no significant difference compared with preoperative data (p = 1). Maneuverability was “very good” in 72.5 % and “good” in 17.5 %, with no significant difference compared with preoperative data (p = 0.92). Two LithoVue broke during surgery (5 %): one occurring in extreme deflection with acute infundibulopelvic angle and spontaneous loss of vision for the second one. Conclusion: The LithoVue displayed good image quality, active deflection and maneuverability. Further evaluation of surgical outcomes and cost analysis will help to present the best utility of this single-use FURS in current practice.
Gesehen am 17.10.2018
Published online: 26 September 2016